MR and CT Arthrography of the Elbow - Delport, Anton G.; Zoga, Adam C. (Seminars in Musculoskeletal Radiology, 2012)
Magnetic resonance (MR) arthrography has, to a great extent, replaced conventional and CT arthrography as the standard of care imaging tool for indications including medial elbow pain in the throwing athlete, chondral and osteochondral lesions in the elbow, and intra-articular bodies. There are still rare specific incidences where CT arthrography is indicated. This article reviews elbow arthrography, with a greater emphasis placed on MR arthrography, including indications, technique, potential complications, contraindications, equipment, and MR arthrographic pathologies.
Keywords: elbow MRI; elbow arthrography; CT arthrography; MR arthrography